An Analysis of the Effectiveness of the Bandung-Kawasaki Gesuido (BKG) project within a Sister City Partnership Framework - Ulung, Alessandro Kurniawan; Saputro, Pradono Budi; Setiawan, Yuli (Jurnal Ilmiah Dinamika Sosial, 2026)
This study examines the effectiveness of the Bandung–Kawasaki Gesuido (BKG) Project within the sister city partnership between the governments of Bandung and Kawasaki. The project aims to facilitate collaboration between the two cities in addressing wastewater management challenges in Bandung. Accordingly, this study poses the following research question: How effective is the BKG Project in implementing the Bandung–Kawasaki sister city partnership? This study applies Kevin O’Toole’s theoretical framework on the phases of sister city partnerships and adopts a mixed-methods approach. Data were collected and analyzed through interviews, questionnaires, observations, and a literature review. Questionnaires were distributed to nearly 200 respondents, including teachers, students, and staff of the Bandung administration. The findings show that the Bandung–Kawasaki partnership is currently in the reciprocative phase, with the BKG Project as its main initiative. At this stage, the BKG Project has been effective in facilitating knowledge transfer from Kawasaki to Bandung. This process enables the Kawasaki government to support capacity development among staff of the Bandung administration, as well as teachers and elementary school students, in improving wastewater management practices in Bandung. The novelty of this research lies in its focus on assessing the BKG Project, making it the first study to do so. This study contributes to the growing body of literature on sister city partnerships in Indonesia and offers insights into ongoing debates about their practical impact and value.